2017
DOI: 10.1155/2017/3831275
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vitamin D Status in a Population of Ecuadorian Subjects

Abstract: Introduction Vitamin D is a preprohormone known to play a key role in phosphocalcic metabolism; its main source comes from the synthesis at the skin level by ultraviolet (UV) radiation. Objective The purpose of this study was to determine the levels of vitamin D in an Ecuadorian population. Materials and Methods Retrospective study of Ecuadorian subjects from the city of Guayaquil, who had an initial study of 25 (OH)-D serum, as the indicator of Vitamin D status, in the period of 2015-2016. Results A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
4
0
4
Order By: Relevance
“…Prevalence of Vitamin D deficiency in Duhok Province, Iraq and females had a higher prevalence of vitamin D deficiency compared to older people and male. Our study is in agreement with the study which is done by Maldonado, et al 28 who demonstrated that the level of vitamin D in older adults is lower than other age groups.…”
Section: Originalsupporting
confidence: 94%
“…Prevalence of Vitamin D deficiency in Duhok Province, Iraq and females had a higher prevalence of vitamin D deficiency compared to older people and male. Our study is in agreement with the study which is done by Maldonado, et al 28 who demonstrated that the level of vitamin D in older adults is lower than other age groups.…”
Section: Originalsupporting
confidence: 94%
“…The average age of the 11,734 patients was 46.5 years, within the middle age group being active in life. The mean serum vitamin D level of the entire population was 16.6 ng/mL, which was <20 ng/mL (deficient range) [2,4,7,15,16]. The mean serum vitamin D level in women was lower than that in men (15.8 ng/mL vs. 19.5 ng/mL, respectively).…”
Section: Main Findingsmentioning
confidence: 99%
“…Por ejemplo, un estudio realizado en las regiones costeras y cordilleras de los Andes del Ecuador mostró una alta prevalencia de deficiencia de vitamina D entre el grupo de mujeres, sujetos indígenas y los residentes en la región de la cordillera de los Andes del país (28). Así mismo, un estudio realizado en la ciudad costera de Guayaquil, Ecuador, mostró que sus participantes presentaban un 70 % de deficiencia de vitamina D; el grupo de ancianos fue el que mayor deficiencia de vitamina D presentó en comparación con otros grupos de edad (29). Otro estudio realizado en mujeres posmenopáusicas ecuatorianas, a quienes se les dividió en dos grupos, uno con diagnóstico de diabetes mellitus tipo 2 y otro sin diagnóstico de la enfermedad, reportó que en el grupo con diabetes el 87,5 % de mujeres tenía insuficiencia de vitamina D frente al grupo sin diabetes, en el que únicamente el 33 % tenía insuficiencia de esta vitamina (17).…”
Section: Discussionunclassified